The Study on the Whole Stress–Strain Curves of Coral Fly Ash-Slag Alkali-Activated Concrete under Uniaxial Compression - Wang, Huailiang (Materials (Basel), 2020)
This study aimed to research the whole stress–strain curves of coral Fly Ash-Slag Alkali-Activated Concrete (CAAC) in different strength grades. Fly ash-slag alkali-activated concrete was used as cementing materials to produce coral aggregate concrete. A monotonic loading test was conducted on the prismatic specimens to obtain elastic modulus (E(c)), Poisson’s ratio (μ) and the constitutive relationship of CAAC under uniaxial compression. When the strain of CAAC reached the maximum value, the specimen was split and damaged rapidly. As the strength grade increased, the ratio of residual stress (σ(ri)) to peak stress (σ(0i)) decreased in the range of 0.17–0.28. The E(c) of CAAC increased gradually, and μ increased to the peak value and then decreased. According to the test results, the constitutive equation of CAAC can be expressed by piecewise expression, which can better reflect all the experimental characteristics. It was also found that CAAC has many similar characteristics with coral concrete and lightweight aggregate concrete. To improve the strength and toughness of CAAC, some fibers, such as organic fiber, can be added to expand the application of CAAC in engineering projects.